Does Subsidized Health Insurance Cause Ex Ante Moral Hazard? Empirical Analysis Of Smoking Intensity In Poor Communities In Indonesia - Rizki Wibias Anwar Maulida; Rus'an Nasrudin (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The existence of ex ante moral hazard (EAMH) can cause inefficiency and threaten the sustainability of the health insurance program developed by the Indonesian government. The deficit in health social funds and the increase in the number of smokers in Indonesia may indicate the presence of EAMH. Several studies have explored EAMH, but their conclusions remain inconclusive. This study will utilize panel data from IFLS waves 2, 3, 4, and 5. By combining matching and Difference-in-Differences (PSM-DiD) methods to eliminate various potential biases, this research aims to reveal the impact of participating in subsidized health insurance on changes in smoking intensity among beneficiaries of Askeskin/JKN PBI. The findings suggest that, overall, the Askeskin policy does not indicate the presence of EAMH in relation to smoking behavior. However, within a specific subset of the data, there are indications of EAMH linked to rising smoking expenses among poor urban individuals.